PENGARUH KEPEMIMPINAN VISIONER KEPALA SEKOLAH, BUDAYA ORGANISASI, DAN KOMPETENSI GURU TERHADAP KOMITMEN KERJA GURU DI SEKOLAH DASAR SWASTA KECAMATAN SAWANGAN KOTA DEPOK - Sofyan Hadi Sofyan Hadi; Lili Nurlaili Lili Nurlaili; Surasni Surasni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
ABSTRACT This study aims to analyze the influence of visionary leadership of school principals, organizational culture, and teacher competence on teachers’ work commitment in private elementary schools in Sawangan District, Depok City. This research employed a quantitative approach using a survey method and regression analysis to examine both partial and simultaneous effects of the variables. The results show that: (1) visionary leadership of school principals has a positive and significant effect on teachers’ work commitment, with a t-value of 11.695 and a significance level below 0.05; (2) organizational culture has a positive and significant effect on teachers’ work commitment, with a t-value of 3.600 (greater than the t-table value of 1.988) and a significance level below 0.05; (3) teacher competence has a positive and significant effect on teachers’ work commitment, with a t-value of 5.851 (greater than the t-table value of 1.982) and a path coefficient of 0.260; and (4) simultaneously, visionary leadership of school principals, organizational culture, and teacher competence have a significant effect on teachers’ work commitment, with a significance level of 0.001 and a contribution of 94.7%.These findings indicate that teachers’ work commitment is strongly influenced by the synergy between visionary leadership, a supportive organizational culture, and professional teacher competence. Therefore, continuous efforts are needed to improve leadership quality, strengthen organizational culture, and enhance teacher competence in order to increase teachers’ work commitment.